How do Individuals with Complete Androgen Insensitivity Syndrome, Mayer-Rokitansky-Küster-Hauser Syndrome or Polycystic Ovary Syndrome Experience Contact to Other Affected Persons? - Krupp, K.; Fliegner, M.; Brunner, F.; Brucker, S.; Rall, K.; Richter-Appelt, H. (Geburtshilfe und Frauenheilkunde, 2012)
Persons with different sex characteristics may suffer from a feeling of being “different” or “not normal”. In this study, persons with one of 3 diagnoses (complete androgen insensitivity syndrome [CAIS]; Mayer-Rokitansky-Küster-Hauser syndrome [MRKHS], polycystic ovary syndrome [PCOS]) were asked whether they had contact to other affected persons and how they assessed this contact. The correlation between contact and psychological distress was evaluated. Material and Methods: Information on contacts to other affected individuals was obtained using a written questionnaire. Psychological distress was measured using the German version of the BSI (Brief Symptom Inventory). Results: Data from 11 individuals with CAIS, 49 women with MRKHS and 55 women with PCOS was analysed. The frequency of contacts to other affected individuals differed between the different diagnostic groups (with the highest frequency reported for the group with CAIS, and the lowest for the group with PCOS). Overall, the majority of individuals considered such contacts beneficial (CAIS 81.8 %; MRKHS 90 %; PCOS 83.3 %). The frequency of contacts and their assessment were not found to be correlated with psychological distress. The three diagnostic groups differed in the proportion of people who indicated a wish for contact with other affected persons. The desire to have contact with other affected persons was most commonly expressed by women with PCOS and high levels of psychological distress (60.9 %). Conclusion: Persons with different sex characteristics can benefit from contact to other affected individuals. Particularly women with PCOS and increased levels of psychological distress may benefit if the issue of support groups is addressed during treatment.
Keywords: Müllerian agenesis; PCOS (polycystic ovary syndrome); CAIS (complete androgen insensitivity syndrome); support group